KAJIAN MAJAS PADA ARTIKEL JURNALISME WARGA SERAMBI INDONESIA - Hendra Kasmi (Jurnal Metamorfosa, 2020)
This research is about the majas reviewing of the citizens Journalism Articles’ in Serambi Indonesia. The problem of this study is to potray the ideas of the majas citizens Articles’ in Serambi Indonesia Journalism. The purpose of this study is to describe the figurative language aspects of the majas in form of the rubric articles in Serambi Indonesia Journalism. The method used is a descriptive analytical method by using a structural approach technique. The data were collected from the articles in the Journalism Citizens of Serambi Indonesia newspaper. The data were analyzed by using qualitative analysis technique. The results of this study indicated that the articles which is found in the citizen journalism in the Indonesia Serambi newspaper contain a lot of figurative languages, such as the experiences of the writer that is written in a free language style. Then, the dominant of the figurative language used in the citizen journalism articles were the personification and metaphorical majas. Abstrak Penelitian ini berjudul Kajian Majas pada Artikel Jurnalisme Warga Serambi Indonesia. Masalah yang ingin ditelaah adalah tentang gambaran majas pada artikel Jurnalisme Warga Serambi Indonesia. Penelitian ini bertujuan mendeskripsikan aspek bahasa kiasan yang terdapat pada artikel-artikel rubrik Jurnalisme Warga di Serambi Indonesia. Metode yang digunakan adalah metode deskriptif analitis dengan pendekatan struktural. Sumber data penelitian ini adalah artikel-artikel rubrik Jurnalisme Warga koran Serambi Indonesia. Data dianalisis dengan menggunakan teknik analisis kualitatif. Hasil penelitian ini menunjukkan bahwa artikel-artikel yang terdapat dalam jurnalisme warga di koran Serambi Indonesia banyak mengandung bahasa kiasan karena tulisan-tulisan artikel tersebut berisi pengalaman penulis yang tentu saja ditulis dengan gaya bahasa bebas. Majas yang dominan terdapat dalam artikel-artikel jurnalisme warga tersebut yakni majas personifikasi dan metafora. Kata Kunci : Majas, Jurnalisme Warga